GIS tool to predict photosynthetically active radiation in a Dry Valley. Issue 5 (October 2020) - Acosta, Dimitri; Doran, Peter T.; Myers, Madeline
Abstract: Understanding primary productivity is a core research area of the National Science Foundation's Long-Term Ecological Research Network. This study presents the development of the GIS-based Topographic Solar Photosynthetically Active Radiation (T-sPAR) toolbox for Taylor Valley. It maps surface photosynthetically active radiation using four meteorological stations with 20 years of data. T-sPAR estimates were validated with ground-truth data collected at Taylor Valley's major lakes during the 2014–15 and 2015–16 field seasons. The average daily error ranges from 0.13 mol photons m -2 day -1 (0.6%) at Lake Fryxell to 3.8 mol photons m -2 day -1 (5.8%) at Lake Hoare. We attribute error to variability in terrain and sun position. Finally, a user interface was developed in order to estimate total daily surface photosynthetically active radiation for any location and date within the basin. T-sPAR improves upon existing toolboxes and models by allowing for the inclusion of a statistical treatment of light attenuation due to cloud cover. The T-sPAR toolbox could be used to inform biological sampling sites based on radiation distribution, which could collectively improve estimates of net primary productivity, in some cases by up to 25%.